Implementación de sistema de control de riego mediante red inalámbrica de sensores de humedad. - Vera Cedeño, Gissela Estefanía (2014)
This work was executed from October 2013 to January 2014 on the grounds of Finca "El Paraiso", belonging to sr. Angel of the Cross, located at km 7/2 via Buena Fe - Quevedo, Los Rios province. He designed and built a system Sprinkler Irrigation that leverages the available water resources of the farm "El Paraiso" efficiently in the agronomic field, as manual watering is removed by an automatic according to the needs of cultivation. The implementation of the system was performed in growing peppers at 3 months of age and results in a modern irrigation system with a high coefficient of uniformity and efficient water consumption was obtained , achieving positive impact among farm employees who they witnessed the final work. Based on the IEEE 802.15.4 standard , each of these devices wireless personal area networks (personal wireless area network , WPAN ) for the transmission of sensor data Moisture each of the plots were used ZIBEE devices are powered by rechargeable batteries which makes installing them. SARIEGO was implemented with three measuring devices located in plots with a distance of 25 meters between each, so three solenoid valves are used to allow the passage of water for each of these sectors according to the individual………………..